Examining the critical success factors in the adoption of value stream mapping - Shou, W.; Wang, J.; Wang, X.; Chong, Heap Yih (2016)
Value Stream Mapping (VSM) is a functional approach to reorganizing production system in line with lean vision. It has been applied in many sectors to improve performance. However, there are several factors that need to be considered while implementing VSM in practice. This paper presents a literature review of the Critical Success Factors (CSFs) in the implementation of VSM across five different sectors: manufacturing, healthcare, construction, product development, and service. The review covers the peer-reviewed journal articles on VSM in Scopus from 1999 to 2015. A four-stage search criteria is designed to refine the publications. 14 CSFs are identified through the deep analysis of the five sectors, and six of them are common success factors, namely, empowered inter-principle lean team, top management, organizational culture, theory refinement and integration, resource availability and communication. The differences of the factors in five sectors are also discussed in this paper. The main limitation of this study is related to the source of the selected papers because conference papers are excluded in this review. The findings of this study provide a good basis for industry practitioners to effectively implement VSM.